2010
DOI: 10.1172/jci42344
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid transport and disease

Abstract: Uric acid is the metabolic end product of purine metabolism in humans. It has antioxidant properties that may be protective but can also be pro-oxidant, depending on its chemical microenvironment. Hyperuricemia predisposes to disease through the formation of urate crystals that cause gout, but hyperuricemia, independent of crystal formation, has also been linked with hypertension, atherosclerosis, insulin resistance, and diabetes. We discuss here the biology of urate metabolism and its role in disease. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
496
1
31

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 669 publications
(554 citation statements)
references
References 105 publications
8
496
1
31
Order By: Relevance
“…Therefore, other contributing factors such as endothelial dysfunction and oxidative stress are also involved in the pathophysiological mechanisms leading to elevated SUA levels and the incidences of hypertension and MetS. [16][17][18] UA potently decreases endothelial nitric oxide bioavailability and induces endothelial dysfunction. 33 Elevated SUA levels were also associated with the increased generation of free radicals 34 and oxidative stress, which could abolish endothelium-dependent vasodilatation, leading to hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, other contributing factors such as endothelial dysfunction and oxidative stress are also involved in the pathophysiological mechanisms leading to elevated SUA levels and the incidences of hypertension and MetS. [16][17][18] UA potently decreases endothelial nitric oxide bioavailability and induces endothelial dysfunction. 33 Elevated SUA levels were also associated with the increased generation of free radicals 34 and oxidative stress, which could abolish endothelium-dependent vasodilatation, leading to hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Confirming the involvement of elevated SUA levels in the pathogenesis of hypertension has been difficult, because MetS can confound the relationship between elevated SUA levels and hypertension and because these conditions share common pathophysiological features, such as insulin resistance, endothelial dysfunction, oxidative stressand inflammation. [16][17][18] For these reasons, controlling for MetS is important in clinical studies that examine the association between elevated SUA levels and the incidence of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…[44][45][46] Studies in rodents and other molecular observations indicate an important role for SLC2A9 in proximal tubular urate absorption. 47,48 Genome-wide (GWAS) and candidate association studies have found strong association of SLC2A9 SNPs with SUA levels. [14][15][16][17][18][19] These studies were mainly conducted in Caucasian, African American and Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 The reabsorption of urate by URAT1 and GLUT9 is inhibited by uricosuric agents such as probenecid and benbromarone, and drugs such as losartan, which have a uricosuric effect. 34,36 An understanding of the physiological effects of urate transporters has led to the development of several drugs that inhibit URAT1. One of them, Lesinurad, is currently in phase 3 clinical trials.…”
Section: Epidemiology Of Goutmentioning
confidence: 99%